2015
DOI: 10.5152/akd.2015.6072
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil serine proteases and their endogenous inhibitors in coronary artery ectasia patients

Abstract: Objective:Proteolytic enzymes possibly contribute to coronary artery ectasia (CAE). This study aimed to determine whether neutrophils, neutrophil serine proteases (NSPs), and their endogenous inhibitors participated in the pathological process of CAE.Methods:The study consisted of 30 patients with CAE, 30 patients with coronary artery disease (CAD), and 29 subjects with normal coronary arteries (Control). The following circulating items were measured: the main NSPs, including human neutrophil elastase (HNE), c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Indeed, cardiac disease has been described in MPS III patients as well as in patients affected by the other MPS subtypes [178,179]. Multiple evidence demonstrated the involvement of CTSs in many cardiovascular diseases, including atherosclerosis, cardiac hypertrophy, cardiomyopathy, myocardial infarction, and hypertension, some of which are common clinical manifestations in MPSs [8,10,[17][18][19]36,56,61,66,76,80,81]. In particular, CTSB results in being up-regulated in cardiomyocytes in response to hypertrophic stimuli both in vivo and in vitro [180].…”
Section: Cathepsin Involvement In the Pathophysiology Of Mucopolysaccmentioning
confidence: 99%
“…Indeed, cardiac disease has been described in MPS III patients as well as in patients affected by the other MPS subtypes [178,179]. Multiple evidence demonstrated the involvement of CTSs in many cardiovascular diseases, including atherosclerosis, cardiac hypertrophy, cardiomyopathy, myocardial infarction, and hypertension, some of which are common clinical manifestations in MPSs [8,10,[17][18][19]36,56,61,66,76,80,81]. In particular, CTSB results in being up-regulated in cardiomyocytes in response to hypertrophic stimuli both in vivo and in vitro [180].…”
Section: Cathepsin Involvement In the Pathophysiology Of Mucopolysaccmentioning
confidence: 99%
“…Previous studies have revealed a potential contribution of trappin‐2 to the pathological process of vascular disorders. For instance, serum trappin‐2 levels are elevated in patients with coronary artery ectasia, and trappin‐2 deposition is abundantly seen in the involved vascular walls of neutrophil‐mediated cutaneous vasculitis . Since SSc is featured by vascular injury and/or vascular activation followed by extensive organ fibrosis, our initial hypothesis was the up‐regulated expression of trappin‐2 in SSc vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that peripheral neutrophil counts and neutrophil-lymphocyte ratios were significantly higher in coronary ectasia patients [ 24 , 25 ]. Inappropriate activation of neutrophils leads to increased levels of neutrophil elastase and neutrophil serine proteases, which increase the degradation of elastin fibres and the transition of collagen from type III to type I in coronary vascular walls [ 26 , 27 ]. At the same time, significant endothelial dysfunction and high oxidative stress were also documented in patients with CAE [ 20 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%